Verso e anverso dos fundamentos contemporâneos dos direitos humanos e dos direitos fundamentais: da localidade do nós à universalidade do outro - Fachin, Melina Girardi (2008)
This dissertation is intended to treat, in a plural and critical way, the complex issue of the foundations of human rights and fundamental rights. The debate is not new, since walk down the tortuous roads of the universality of rights and cultural relativism transport us back to the very origin - and genealogy of those rights. However, in the contemporary global scenario, this subject arises with strength. This is because for the theory of human rights and fundamental rights has been particularly difficult to deal with the world that emerges from the clash of civilizations, which marks the beginning of the new millennium. The structures and categories, in theory, and in a practical level, were designed in the light of the dichotomy us/them. In this multicultural scene, raise the challenge of targeting human rights and fundamental rights as a policy both global and cultural, as theoretical artifacts of possible universality, which instead of being hegemonic instruments, are open and influenced by cultural reality. To fulfill this mission, it is important the analysis of the emergence of both the history and evolution of the universalism and relativist matrix in legal discourse. Also important is to mirror this debate by international decisions, which have been confronted by such demands. Currently, there are several possible, though contradictory, answers to the demand. The challenge, that the work will explore, is think its limits and possibilities beyond a single answer